The use of shape memory alloys in fuses for the protection of electrical installations - Kozyrskyi, V. V.; Nurek, T.; Sloma, J.; Bunko, V. Ya.; Goncharuk, M. V. (Національний технічний університет "Харківський політехнічний інститут", 2026)
The degree of damage to electrical installations during short circuits depends on the response time of the protection. An effective way to enhance the current-limiting effect in electrical fuses (reducing their response time) may be the use of shape memory alloy (SMA) elements. However, this requires careful study and research. The goal of the work is to establish the patterns of strengthening the current-limiting effect of a fuse (reducing the response time) when using thermosensitive elements made of shape memory alloys.

Ступінь пошкодження електроустановок при коротких замиканнях залежить від часу спрацювання захисту. Ефективним способом покращення струмообмежуючого ефекту в електричних запобіжниках (зменшення часу їх спрацювання) може бути застосування елементів із сплавів з ефектом пам'яті форми. Проте, це потребує ретельного вивчення та дослідження.
Keywords: functional materials; fuse; shape memory alloy; thermosensitive element; термочутливий елемент; запобіжник; функціональні матеріали; сплави; математичні моделі; струмові навантаження